2018
DOI: 10.4103/digm.digm_41_17
|View full text |Cite
|
Sign up to set email alerts
|

Eye state classification from electroencephalography recordings using machine learning algorithms

Abstract: Background and Objectives: Current developments in electroencephalography (EEG) foster medical and nonmedical applications outside the hospitals. For example, continuous monitoring of mental and cognitive states can contribute to avoid critical and potentially dangerous situations in daily life. An important prerequisite for successful EEG at home is a real-time classification of mental states. In this article, we compare different machine learning algorithms for the classification of eye states ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The classification error rate for a study 31 is very large, that is, 27.39%, as compared to 2.73% as computed for LR in our work. Very good performance in terms of classification accuracy has been achieved by the studies as, 97.5%, 34 99.8%, 39 97%-99%, 38 97.4%, 32 97.3%, 30 88.2%, 36 and 84.05%, 33 but all of them have explored very smaller datasets, that is, data from only a single subject has been used in the studies 30,[32][33][34]36,39 and data from 27 subjects in a study. 38 For the studies 29,37 based upon 11 subjects and 50 subjects, respectively, no classification accuracies have been computed by them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The classification error rate for a study 31 is very large, that is, 27.39%, as compared to 2.73% as computed for LR in our work. Very good performance in terms of classification accuracy has been achieved by the studies as, 97.5%, 34 99.8%, 39 97%-99%, 38 97.4%, 32 97.3%, 30 88.2%, 36 and 84.05%, 33 but all of them have explored very smaller datasets, that is, data from only a single subject has been used in the studies 30,[32][33][34]36,39 and data from 27 subjects in a study. 38 For the studies 29,37 based upon 11 subjects and 50 subjects, respectively, no classification accuracies have been computed by them.…”
Section: Discussionmentioning
confidence: 99%
“…Saghafi et al 36 proposed an algorithm that could perform an EEG eyes state change detection in less than 2 s that was the significant improvement over the Rösler and Suendermann 30 work; Hussain et al 37 found multi‐scale permutation entropy as the useful parameter in differentiating the EEG signals for the binary eyes states‐closed and opened; Piatek et al 38 performed three‐states (eyes open, eyes close, and blinking) classification using 23 different machine learning methods and obtained good performance in terms of classification accuracy, training time, classification time, and complexity; Zhou et al 39 developed an efficient eyes state classification system that gave excellent performance results in terms of classification speed and accuracy; Karamacoska et al 40 adopted the principal component analysis for the EEG and event‐related potential (ERP) components to examine the resting state conditions in relation to performing an auditory go and no‐go tasks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our case, no pre-selection of the signal was done when applying the proposed methodology. Other authors do select the best segments to build their dataset, which is not applicable in real-time systems; for example, Piątek et al ( 2018 ) obtained an accuracy of over 96% with different classification algorithms with a time window of 10 s.…”
Section: Discussionmentioning
confidence: 99%